Glacier surface velocities of Hintereisferner, 2023/2024 - Martin Stocker-Waldhuber; Bernd Seiser; Lea Hartl; Giulia Bertolotti; Andreas Gschwentner; Andrea Fischer (PANGAEA, 2025)
Glacier surface velocities are measured on four neighbouring glaciers in the Ötztal Alps (Austria). Measurements of the annual horizontal flow velocity (Δs/a [m/a]) on Hintereisferner (HEF) were started in 1885 at stone lines (cross-profiles). Annual values for the stone lines are given as mean values from the stones at the cross-profiles. On Kesselwandferner, the annual horizontal (Δs/a [m/a]) and vertical velocities (Δv/a [m/a], positive upwards and negative downwards) are measured at ablation and accumulation stakes since 1965. On Taschachferner (TSF) and Gepatschferner (GPF), the records of annual and subseasonal horizontal flow velocities at ablation stakes were started in 2009. This data series is a continuation of: doi:10.1594/PANGAEA.896741
In: Stocker-Waldhuber, Martin; Fischer, Andrea; Helfricht, Kay; Kuhn, Michael; Schneider, Heralt; Span, Norbert (2021): Glacier surface velocities in the Ötztal Alps (Austria), 2017 et seq [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.928360